Stressful Life Events Severity in Patients with Depressive Disorder: A Cross-Sectional Study - Niroula, Riju; Silwal, Pooja (Journal of Psychiatrists' Association of Nepal, 2022)
Introduction: Stress and stressful life events are believed to precipitate depressive disorders but the areas of stress and types of stressful life events found in depression vary by socio-cultural contexts. So this study was conducted to assess the contribution of the number and severity of recent stressful life events on the prevalence of depressive disorder in a tertiary hospital in Nepal. Methodology: 237 consecutive patients with ICD-10 diagnosis of a depressive disorder were included in the study. The Beck Depression Inventory (BDI) was applied to rate the severity of depressive disorder and The Social Readjustment Rating Scale (SRRS) was applied to assess for the severity of stressful life events. Result: 65.8% patients had experienced low severity of Stressful life events SLEs while 13.5% patients suffered from medium severity of SLEs and 20.6% suffered from severe SLEs. Severity of depression assessed with BDI revealed the 62.8% patients suffered from moderate depression while 22.7% suffers from severe depression. The Chi square statistics showed statistically significant difference on age, marital status, educational status and socioeconomic status. Also the severity of depression was found to be statistically significant with severity of SLEs experienced. Conclusion: Significant correlation was seen between severity of depressive disorder and stressful life events. Establishing their impact and addressing coping mechanisms should be done to make for a comprehensive management of any patient diagnosed with depressive disorder.